PARALLEL TEXTS AS AN AUXILIARY TOOL IN THE PROCESS OF (SPECIALIST) TRANSLATION - KUBACKI, Artur Dariusz (Comparative Legilinguistics, 2013)
The article contains an analysis of parallel texts as an auxiliary tool in the process of specialist translation. The translation of professional texts with the use of parallel texts as the primary source and dictionaries only as the secondary source is nowadays a widely adopted strategy. At the beginning of the article, the author discusses different definitions of a parallel text proposed by Polish and German researchers. In academic literature, various terms are used for parallel texts, for instance opposite, intermediary, base, supplementary or model texts. These types of texts fulfil different functions and might be subject to analysis at various stages. In the next part of the article, the author discusses the advantages and disadvantages of (specialist) translation with the use of parallel texts and presents the methods of finding parallel texts in the field of law. Finally, he describes the results of an experiment conducted for this article in a private school for specialist translators. The experiment fully confirmed the usefulness of parallel texts in the process of translation.